Analyses of the soluble levels of sCD40L, sCD62P and sCD40 in pediatric sickle cell anemia patients with abnormal transcranial Doppler - Cinthya Pereira Leite Costa de Araújo; Maria do Carmo Menezes Bezerra Duarte; Leuridan Cavalcante Torres (Hematology, Transfusion and Cell Therapy, 2024)
Introduction: Serum levels of sCD40L, sCD40 and sCD62P were evaluated in sickle cell anemia (SCA) patients aged between 2 and 16 years with normal transcranial Doppler (TCD) and no stroke (G1, n = 24); in SCA patients with abnormal TCD (G2, n = 16); in SCA patients with a previous history of stroke (G3, n = 8), and; in healthy controls (aged 2 to 13 years; n = 26). Results: The levels of sCD40L were significantly higher in the G1, G2 and G3 groups, compared to controls (p = 0.0001, p < 0.0002 and p = 0.004, respectively). Among patients with SCA, higher levels of sCD40L were found in the G3 group, compared to the G2 group (p = 0.03). In the sCD62P analysis, high levels in G3, compared to G1 (p = 0.0001), G2 (p = 0.03) and G4 (p = 0.01), and G2 also had high levels, compared to G1 (p = 0.04). The G1 patients had a higher sCD40L/sCD62P ratio, compared to G2 (p = 0.003) and controls (p < 0.0001). The sCD40L/sCD40 ratios were higher in G1, G2 and G3, compared to controls (p < 0.0001, p = 0.008 and p = 0.002, respectively). Conclusion: It was concluded that the combination of TCD abnormality, associated with levels of sCD40L and sCD62P, may contribute to a better assessment of the risk for stroke in pediatric SCA patients.Favor pedir para os autores corrigirem esta frase, pois NÃO é uma sentença completa em inglês: Our data suggest that decreased values of the s[LSM1] CD40L/sCD62P ratio involving two inflammatory mediators produced in platelet activation, being unprecedented in the literature.